+0  
 
0
105
1
avatar

how do you complete the square of \(a^2-ap+p^2-3q\) ?

 May 11, 2020
 #1
avatar+112185 
+2

a^2  - ap   +  p^2  - 3q

 

We will consider  "a"  as  the  variable of  interest

 

We can write

 

a^2  + pa   =   3q   - p^2

 

Take  (1/2)  of p  =   p/2       square this  =  p^2 / 4        add to both sides

 

a^2  +pa + p^2/4  =  3q - p^2  + p^2/4

 

Factor  the  left side  simplify the right

 

(a  + p/2)^2  =    [ 12q - 4p^2 + p^2 ]  / 4

 

Take  both   roots

 

(a + p/2)  =  ±√ [ 12q  - 3p^2 ] / 2 

 

Subtract p/2  from both sides

 

a  = ±√ [ 12q - 3q^2 ]  / 2   - p/2

 

a =   - p ±√[12q - 3q^2]

        _________________

                2

 

 

cool cool cool

 May 11, 2020

14 Online Users